Towards a Just Transition in Ireland and the European Union: A critical overview of the policy frameworks - Mandelli Matteo; Murphy Mary (Administration)
This article is primarily a scene-setting one, which aims to give the reader both European Union (EU) and Irish institutional and policy context for this special edition. It presents and discusses the EU and national institutional and policy contexts relevant to the Just Transition (JT) and addresses relevant aspects and issues. Our interest is in the institutions and policies that shape or limit our capacity to change the conversation to what is needed to advance a transformational agenda that conjoins climate and equality as twin goals and enables integrated and inclusive governance. Our focus on the JT is because, as a concept, it interfaces climate policy and social justice.